Multisite Phosphorylation of NuMA-Related LIN-5 Controls Mitotic Spindle Positioning in C. elegans - Portegijs, Vincent (PLoS Genet, 2016)
During cell division, the mitotic spindle segregates replicated chromosomes to opposite poles of the cell, while the position of the spindle determines the plane of cleavage. Spindle positioning and chromosome segregation depend on pulling forces on microtubules extending from the centrosomes to the cell cortex. Critical in pulling force generation is the cortical anchoring of cytoplasmic dynein by a conserved ternary complex of Gα, GPR-1/2, and LIN-5 proteins in C. elegans (Gα–LGN–NuMA in mammals). Previously, we showed that the polarity kinase PKC-3 phosphorylates LIN-5 to control spindle positioning in early C. elegans embryos. Here, we investigate whether additional LIN-5 phosphorylations regulate cortical pulling forces, making use of targeted alteration of in vivo phosphorylated residues by CRISPR/Cas9-mediated genetic engineering. Four distinct in vivo phosphorylated LIN-5 residues were found to have critical functions in spindle positioning. Two of these residues form part of a 30 amino acid binding site for GPR-1, which we identified by reverse two-hybrid screening. We provide evidence for a dual-kinase mechanism, involving GSK3 phosphorylation of S659 followed by phosphorylation of S662 by casein kinase 1. These LIN-5 phosphorylations promote LIN-5–GPR-1/2 interaction and contribute to cortical pulling forces. The other two critical residues, T168 and T181, form part of a cyclin-dependent kinase consensus site and are phosphorylated by CDK1-cyclin B in vitro. We applied a novel strategy to characterize early embryonic defects in lethal T168,T181 knockin substitution mutants, and provide evidence for sequential LIN-5 N-terminal phosphorylation and dephosphorylation in dynein recruitment. Our data support that phosphorylation of multiple LIN-5 domains by different kinases contributes to a mechanism for spatiotemporal control of spindle positioning and chromosome segregation.